PENGOLAHAN CITRA DIGITAL PERBANDINGAN METODE HISTOGRAM EQUALIZATION DAN SPESIFICATION PADA CITRA ABU-ABU - yelly y nabuasa (Universitas Nusa Cendana, 2019)
A digital image processing software has been successfully constructed. The software can increase image contrast using the histogram equalization method. The results given by the equalizaton histogram method can improve image quality, so that the information in the image is more clearly seen. But not all digital images have a visual display that satisfies the human eye. Dissatisfaction can arise due to noise, the lighting quality in digital images that are too dark or too bright. So that a method is needed to improve the quality of the digital image. To improve image quality in terms of color contrast, we can give treatment to the histogram. The treatment referred to in this article is an equalization histogram on grayscale images. Image histogram is said to be good if it is able to involve all possible levels or levels at the gray level. Of course the goal is to be able to display details on the image so that it is easy to observe. The process of segmenting and repairing digital images is done using MATLAB.